Effect of Covid-19 on Premature Birth : A Systematic Review and Meta-Analysis - Anita Dewi Anggraini; Budi Prasetyo; Rachmah Indawati (Institute of Computer Science (IOCS), 2022)
COVID-19 is growing very rapidly and spreading across the globe. Pregnant women are group at risk of being infected by COVID-19. Premature birth is as a major contributor to death in early life. The purpose of this study was to determine the relationship between pregnant women infected with COVID-19 with the incidence of premature birth.This study used the PRISMA checklist. The PECOS framework was used as a search strategy tool. Search literature was using 3 databases consisting of Pubmed, Spinger, and Proquest. The quality of the articles screened was assessed by using The Joanna Briggs Institute Critical Appraisal tools was applyed in JBI Systematic Reviews in 2017. The results of the study show that there is a significant relationship between COVID-19 and Premature labor with p value < 0.00001. Pregnant women with COVID-19 have a 1.48 times risk of experiencing Premature birth compared to those who are not infected with COVID-19 (OR 1.48 (95% CI 1.16 - 1.90)).